Holistic Paradigm In Islamic Education: A Tafsir Tarbawi Study Of Q.S. Al-Qashash Verse 77 - Sya'ban, Bildan Muhammad; Surahman, Cucu; Sumarna, Elan (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
This article aims to explore the holistic paradigm in Islamic education through a Tarbawi Tafsir study of QS Al-Qashash verse 77, which emphasizes the importance of balance between worldly life and the hereafter and encourages good deeds. This research employs a qualitative approach using literature study methods, with the primary data source being the Qur’an, and secondary sources including various classical and contemporary tafsir texts as well as relevant journal articles. The results indicate that the holistic paradigm in Islamic education can shape individuals who are balanced in academic knowledge and character, and who play active roles in society. The conclusion of this study is expected to strengthen the holistic paradigm aligned with the principle of balance as outlined in QS Al-Qashash verse 77 and to be applicable in everyday life.